Innovating the Wood Sector: A Case Study in Alta Floresta do Oeste, RondAnia State (Brazil) (Global Journal of Management and Business Research, 2014)
This article is about the innovation on management of the stock in a wood company focus in acquisition and program on the productivity process. The lack of publication involving this subject is the reason to study that the problem in the professional workplace and contributes in the business management, engineering, economy, environment and others. The goal of this paper is to discuss and join the information about the forestry products and the logistic used in the wood industry. This involves questions on logistic, stock program-mming and buying of raw material. The hope is to improve the procedure of this sector allowing cost reduction, quality in decision and critical view about the performance, with systemic perception that can be used with the innovation in this type of companies. The answer is found in the conti-ngency theory, through the application of the Method of Case Study with its regular procedure. As a result is offered a theoretical, technical and conceptual support on what this researched wood manager is practicing. Recommendations are offered to continuous improvement and economical, social and environmental viability in this sector.
Keywords: administration; acquisition; stock; programming; wood manufacturing